Nicosulfuron Degradation by an Ascomycete Fungus Isolated From Submerged Alnus Leaf Litter - Carles, Louis; Rossi, Florent; Besse-Hoggan, Pascale; Blavignac, Christelle; Leremboure, Martin; Artigas, Joan; Batisson, Isabelle (Frontiers in Microbiology, 2018)
Nicosulfuron is a selective herbicide belonging to the sulfonylurea family, commonly applied on maize crops. Its worldwide use results in widespread presence as a contaminant in surface streams and ground-waters. In this study, we isolated, for the first time, the Plectosphaerella cucumerina AR1 nicosulfuron-degrading fungal strain, a new record from Alnus leaf litter submerged in freshwater. The degradation of nicosulfuron by P. cucumerina AR1 was achieved by a co-metabolism process and followed a first-order model dissipation. Biodegradation kinetics analysis indicated that, in planktonic lifestyle, nicosulfuron degradation by this strain was glucose concentration dependent, with a maximum specific degradation rate of 1 g/L in glucose. When grown on natural substrata (leaf or wood) as the sole carbon sources, the Plectosphaerella cucumerina AR1 developed as a well-established biofilm in 10 days. After addition of nicosulfuron in the medium, the biofilms became thicker, with rising mycelium, after 10 days for leaves and 21 days for wood. Similar biofilm development was observed in the absence of herbicide. These fungal biofilms still conserve the nicosulfuron degradation capacity, using the same pathway as that observed with planktonic lifestyle as evidenced by LC-MS analyses. This pathway involved first the hydrolysis of the nicosulfuron sulfonylurea bridge, leading to the production of two major metabolites: 4,6-dimethoxypyrimidin-2-amine (ADMP) and N,N-dimethyl-2-sulfamoylpyridine-3-carboxamide (ASDM). One minor metabolite, identified as 2-(1-(4,6-dimethoxy-pyrimidin-2-yl)-ureido)-N,N-dimethyl-nicotinamide (N3), derived from the cleavage of the C-S bond of the sulfonylurea bridge and contraction by elimination of sulfur dioxide. A last metabolite (N4), detected in trace amount, was assigned to 2-(4,6-dimethoxy-pyrimidin-2-yl)-N,N-dimethyl-nicotinamide (N4), resulting from the hydrolysis of the N3 urea function. Although fungal growth was unaffected by nicosulfuron, its laccase activity was significantly impaired regardless of lifestyle. Leaf and wood surfaces being good substrata for biofilm development in rivers, P. cucumerina AR1 strain could thus have potential as an efficient candidate for the development of methods aiming to reduce contamination by nicosulfuron in aquatic environments.